Atividade eletromiográfica durante exercícios de propriocepção de tornozelo em apoio unipodal - CALLEGARI, Bianca (2015)
Proprioception refers to the ability of mechanoreceptors to discriminate body position and joint movements, as well as tensions during static or dynamic phases. The aim of this study was to assess, by means of surface electromyography, activation patterns of the gastrocnemius and tibialis anterior muscles in proprioception exercises, also comparing difficulty levels. Fifty-four sedentary, right-handed, 20-to-35 year-old male volunteers performed single-leg stance exercises on the balance board, wobble board, elastic trampoline and on the floor, at the rate of three 15-second repetitions each, with a 15-second interval between repetitions. After the exercises, volunteers pointed out the highest difficulty felt. Electrical activity of both muscles was significantly higher during the test on the balance board. On the floor, both muscles showed less activity, but only for gastrocnemius muscle this difference was significant. No differences were found in muscle activation during exercises on the wobble board and the elastic trampoline. Inter-muscle analysis showed greater activity of the tibialis anterior muscle, except on the balance board. This study suggests that, when planning one-leg stance exercise for proprioceptive training, the balance board is the equipment that most requires activation of gastrocnemius and tibialis anterior muscles, being also the most difficult one.